Depression, anxiety, coping skills and quality of life among pre-university students in Kuantan Pahang - Mohd Arifin, Siti Roshaidai; Yuhasri’Azan, Aisyah Wahidah; Kamaruddin, Amalia; Mohd Mohadis, Hazwani; Abd. Aziz, Karimah Hanim; Musa, Ramli; Muhammad, Noor Azimah; Abang Abdullah, Khadijah Hasanah; Syed Mohideen, Fathima Begum; Marhusin, Mohd Fadzli; Che Mat, Khairi; Mohd Noor, Hanisah; et al. (Universiti Putra Malaysia Press, 2025)
Introduction: In recent years, the increasing prevalence of mental disorders, such as depression and anxiety, among pre-university students has raised significant concern. This study investigates the association between depression, anxiety, coping skills, and quality of life within this population. Methods: A quantitative cross-sectional survey was conducted at a pre-university college in Kuantan, Pahang. Participants were selected based on the inclusion and exclusion criteria. The questionnaire consisted of Depression Anxiety and Stress Scale (DASS-21) questionnaires, coping skills and quality of life questionnaires, and were distributed to all faculties by the Students Representative Council through an online platform. Data were analysed using descriptive studies, Mann-Whitney test, and Pearson Correlation Coefficient. Results: A total of 309 participants responded to the online survey. The study found that prevalence of depression and anxiety were 63.8% and 77.3% respectively. The mean (SD) of the total score for coping skills was 41.90 (SD±9.21) with a minimum score of 15 and a maximum score of 65 while the mean (SD) for quality of life was 76.90 (SD±17.62) with a minimum score of 35 and a maximum score of 115. Total coping skills scores have significant correlations with quality of life (p < 0.001). Depression and anxiety showed significant association with quality of life with a p-value of 0.001 and p-value of 0.001 respectively. Conclusion: Preventive measures and intervention programs for pre-university students should be planned immediately towards reducing the prevalence of mental disorders.